2020
DOI: 10.1016/j.ijppaw.2020.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Trichuris species eggs from non-human primates by geometric morphometric analysis

Abstract: Human trichuriasis is a neglected tropical disease which affects millions of people worldwide, mostly living in low socio-economic conditions. Numerous studies have been conducted over the past 10 years to compare the different techniques for T. trichiura eggs detection. Our study provides the first geometric morphometric analysis for the specific detection of eggs of Trichuris sp. isolated from stools of macaque ( M. sylvanus) , colobus ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Recently, the morphometric approach analyzing the adult worms and eggs of Trichuris spp. of non-human primates were analyzed [33,34]. Morphometric data on the adult worms showed that features present in the females made them indistinguishable for species characteristics, but adult male worms may be used to differentiate Trichuris populations [33].…”
Section: Trichuriasis Of Manmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the morphometric approach analyzing the adult worms and eggs of Trichuris spp. of non-human primates were analyzed [33,34]. Morphometric data on the adult worms showed that features present in the females made them indistinguishable for species characteristics, but adult male worms may be used to differentiate Trichuris populations [33].…”
Section: Trichuriasis Of Manmentioning
confidence: 99%
“…present in non-human primates. However, further data must be collected to determine the sensitivity and specificity of this diagnostic tool [34]. Combination of various techniques, such as the use of molecular and morphological analysis, should be performed for confirmation of various Trichuris spp.…”
Section: Trichuriasis Of Manmentioning
confidence: 99%
“…In previous studies, the influence of the geographical location or host species on the size of helminth adults and eggs has been reported, for example, in species of Fasciola (Valero et al , 2001, 2002, 2009, 2012, 2018; Ashrafi et al , 2015) or Trichuris (Garcia-Sánchez et al , 2019, 2020). Nevertheless, these phenomena have so far not been described in the genus Calodium .…”
Section: Discussionmentioning
confidence: 94%
“…For this reason, new tools should be applied to advance in diagnostics. Furthermore, morphological analyses are necessary to complement molecular techniques (Valero et al , 2001, 2009, 2012; García-Sánchez et al ., 2019, 2020; Reguera-Gomez et al , 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Primate stool samples were collected, smeared onto glass slides, covered with coverslips, and recorded using photographs taken under a light microscope. The pictures were uploaded into a computer program, scaled, and digitized, and the shape patterns were statistically analyzed using principal component analysis, canonical variate analysis, and Mahalanobis distance [ 65 ]. In addition, Hugot and Baylac (2007) identified pinworms (Enterobiinae) using a landmark analysis [ 47 ].…”
Section: Advanced Approaches For Medical Parasite and Arthropod Diagnosesmentioning
confidence: 99%